Honduras : Investment Climate Assessment, Volume 2. Main Report - World Bank (Washington, DC, 2013)
The 21st century reality is that Honduras does not compete only with its Central American and Latin neighbors. Thanks to the ongoing Central American Free Trade Agreements (CAFTA) negotiations, the country will have the opportunity to accelerate the pace of its integration into the global economy. Improving the investment climate is essential for Honduras to take advantage of the opportunities provided by CAFTA, attract foreign investment, diversify exports and increase growth. This report identifies the critical constraints on private sector productivity and growth in Honduras, and provides policy recommendations for addressing them, including a summary of the Government's ongoing and planned initiatives and some additional suggestions. The diagnostic is based on the results of a survey of a stratified sample of 450 Honduran manufacturing firms. The report focuses on four key areas of the investment climate: (1) governance, (2) infrastructure, (3) innovation, quality certification and labor skills; and (4) finance. Overall results of the ICS and of an econometric analysis based on the results of the survey show that bottlenecks in all four investment climate variables increase Honduran firms' costs of doing business and reduce their productivity. The first chapter presents on overview of the structure of the Honduran economy, while each of the other four chapters analyzes the findings of the Investment Climate Survey and provides policy recommendations in one of the four areas of the investment climate. Constant Government progress to reduce constraints on economic growth, as well as firms' dynamic pursuit of new markets and innovation, are both essential in order for the country to take advantage of the opportunities offered by the new trade agreements, improve growth, and fulfill social expectations. Improving the investment climate in Honduras will require cross sector strategies and actions geared towards aligning economic policy, public management, infrastructure, technology, foreign direct investment (FDI), innovation, training and finance policies.